2013
DOI: 10.1523/jneurosci.0034-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Depression of Synaptic Kainate Receptors Reduces Excitability by Relieving Inhibition of the Slow Afterhyperpolarization

Abstract: Kainate receptors (KARs) are ionotropic glutamate receptors that also activate noncanonical G-protein-coupled signaling pathways to depress the slow afterhyperpolarization (sAHP). Here we show that long-term depression of KAR-mediated synaptic transmission (KAR LTD) at rat hippocampal mossy fiber synapses relieves inhibition of the sAHP by synaptic transmission. KAR LTD is induced by high-frequency mossy fiber stimulation and natural spike patterns and requires activation of adenosine A 2A receptors. Natural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…We next studied whether endogenous adenosine released by high‐frequency electrical stimulation is sufficient to modulate hippocampal pyramidal cell discharge through adenosine A 2A R (Chamberlain et al, ). We utilized experimental design used above in Figure to electrically stimulate Schaffer collaterals with paired pulses (50 ms interval), while recording field potential in the CA1 area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next studied whether endogenous adenosine released by high‐frequency electrical stimulation is sufficient to modulate hippocampal pyramidal cell discharge through adenosine A 2A R (Chamberlain et al, ). We utilized experimental design used above in Figure to electrically stimulate Schaffer collaterals with paired pulses (50 ms interval), while recording field potential in the CA1 area.…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine A 2A R‐mediated modulation of neuronal activity has also been reported in the hippocampus and neocortex where the receptor activation facilitates excitatory input from the CA3 area to CA1 enhancing glutamatergic synapses directly or by altering glutamate transport (Cunha et al, ; Rebola et al, ; Dias et al, ; Matos et al, ). In physiological conditions adenosine A 2A Rs are involved in synaptic long‐term plasticity in hippocampal glutamatergic mossy fibers (Rebola et al, ; Chamberlain et al, ), and a recent study demonstrated that deletion of A 2A R selectively in the hippocampus compromizes contextual memory formation (Wei et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Time to first spike was measured from the first stimulus in the train. Post synaptic potential (PSP) envelope was measured by calculating the area under the curve generated by joining the points of maximum hyperpolarisation in response to each stimulation as described previously (Chamberlain et al, 2013). Carbachol (CCh 10 µM) -induced depolarisations were neutralised by current injections to maintain a constant membrane voltage (i≠0).…”
Section: Methodsmentioning
confidence: 99%
“…; Chamberlain et al . ; Rau et al . ) and augments long‐term potentiation (LTP) (D'Alcantara et al .…”
Section: Cellular Mechanisms Underlying A2ar‐mediated Neurodegenerationmentioning
confidence: 99%
“…According to the classical view of neuronal damage as resulting from glutamate excitotoxicity (see Choi 1992;Lipton and Rosenberg 1994;Mattson 2003), neuronal A 2A R could be pivotal in the control of neurodegeneration. In fact, A 2A R are mainly located in glutamatergic synapses (Rebola et al 2005b;Rodrigues et al 2005;Costenla et al 2011), as a result of their ability to avidly bind SAP102 (synapseassociated protein 102) (Thurner et al 2014), and selectively activate principal neurons rather than interneurons in the hippocampus (Rombo et al 2015); A 2A R activation increases the entry of calcium through voltage-sensitive calcium channels (Gubitz et al 1996;Gonc ßalves et al 1997;Murphy et al 2003;Higley and Sabatini 2010;Noronha-Matos et al 2011;Wong and Schlichter 2014), bolsters the evoked release of glutamate (Lopes et al 2002;Marchi et al 2002;Rodrigues et al 2005;Ciruela et al 2006a;Shen et al 2013;Matsumoto et al 2014;Machado et al 2016), enhances the activity of ionotropic glutamate receptors (Dias et al 2012;Di Angelantonio et al 2015), namely of NMDA receptors (Wirkner et al 2004;Guntz et al 2008;Rebola et al 2008;Azdad et al 2009;Higley and Sabatini 2010;Scianni et al 2013;Sarantis et al 2015), depolarizes neurons (Li and Henry 1998;Ponzio et al 2006;Chamberlain et al 2013;Rau et al 2015) and augments long-term potent...…”
Section: Neuronal a 2a R And Neuroprotectionmentioning
confidence: 99%